2021
DOI: 10.2147/cia.s289479
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Potential Differentially Expressed miRNAs and mRNAs in Osteonecrosis of the Femoral Head Based on Integrated Analysis

Abstract: Purpose Osteonecrosis of the femoral head is a common disease of the hip that leads to severe pain or joint disability. We aimed to identify potential differentially expressed miRNAs and mRNAs in osteonecrosis of the femoral head. Methods The data of miRNA and mRNA were firstly downloaded from the database. Secondly, the regulatory network of miRNAs–mRNAs was constructed, followed by function annotation of mRNAs. Thirdly, an in vitro experiment was applied to validate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…miR-148a-3p [ 17 ], miR-23b-3p [ 18 ], and miR-26a [ 19 ] were all reported to play a protective role against ONFH. Recent advancement of genome-wide profiling approaches, such as gene microarray and RNA-sequencing technology, enhances the understanding of miRNA and gene expression profiles in the context of ONFH, providing opportunity to identify novel biomarkers and therapeutic targets for ONFH [ 20 , 21 ]. However, previous miRNA and gene expression profiles studies in ONFH are limited and focused one or several of the differentially expressed miRNAs (DEmiRs) or differential expressed genes (DEGs); none of them focused on the cooperative miRNA-mRNA regulatory mechanism for the pathogenesis of ONFH.…”
Section: Introductionmentioning
confidence: 99%
“…miR-148a-3p [ 17 ], miR-23b-3p [ 18 ], and miR-26a [ 19 ] were all reported to play a protective role against ONFH. Recent advancement of genome-wide profiling approaches, such as gene microarray and RNA-sequencing technology, enhances the understanding of miRNA and gene expression profiles in the context of ONFH, providing opportunity to identify novel biomarkers and therapeutic targets for ONFH [ 20 , 21 ]. However, previous miRNA and gene expression profiles studies in ONFH are limited and focused one or several of the differentially expressed miRNAs (DEmiRs) or differential expressed genes (DEGs); none of them focused on the cooperative miRNA-mRNA regulatory mechanism for the pathogenesis of ONFH.…”
Section: Introductionmentioning
confidence: 99%
“…Hao et al [ 99 ] identified 24 differentially-expressed miRNAs associated with 457 mRNAs in blood samples of ONFH individuals; some of the most representative upregulated miRNAs were hsa-miR-378c, hsa-miR-3200-3p, hsa-miR-28-5p, hsa-let-7a-5p, hsa-miR-3200-5p, and hsa-miR-532-5p. Moreover, it was observed that hsa-miR-378-c could downregulate WNT3A, DACT1, and CSF1, suggesting its possible role in regulating angiogenesis and bone remodeling.…”
Section: Osteonecrosis and Mirnasmentioning
confidence: 99%
“…Likewise, it was suggested that hsa-let-7a-5p could have a crucial role in ONFH progression due to the fact that this miRNA targets RCAN2 and IL9R, which are proteins involved in bone development and hematopoietic cell lineage, correspondingly. Finally, it was demonstrated that hsa-miR-532-5p could hinder the expression of CLDN18 and CLDN10 ( Figure 4 ), which might be implicated in ONFH bone loss [ 99 ].…”
Section: Osteonecrosis and Mirnasmentioning
confidence: 99%
“…Zhang, Chen, et al, 2018), and it has been tested to be related with osteogenic differentiation (Guo et al, 2020). As reported, miR-532-5p is upregulated in ONFH (Hao et al, 2021); however, its role and molecular mechanism in ONFH still need to be further explored.…”
Section: Introductionmentioning
confidence: 99%